Perception of moderate-intensity physical activity by onset of obesity: A randomized crossover trial - Rupp, Kristie; Stewart, Andrea L.; Friel, Ciarán P. (Clinical Obesity, 2022)
Moderate-intensity physical activity is recommended for inactive adults with overweight/obesity (OW/OB). The objective of this study is to determine if differences exist in the selection of moderate intensity between inactive adults with juvenile-onset (JO) and adult-onset (AO) OW/OB. Participants (JO = 18, AO = 20) were stratified by onset and completed two separate 20-minute moderate-intensity exercise sessions on a treadmill and cycle ergometer (randomized order). Multiple linear regression was used to determine whether exercise intensity (average METS, % age-predicted HRmax), self-reported pleasure or exertion differed by onset, controlling for age and gender. On the treadmill, JO and AO participants selected an average intensity of (mean [SD]) 3.5 (0.9) and 3.7 (0.9) METS, and 64.0 (7.7) and 64.9 (7.5) % of age-predicted HRmax, respectively. On the cycle, JO and AO participants selected an average intensity of 3.3 (0.9) and 3.3 (1.0) METS, and 65.2 (8.8) and 60.7 (7.2) % of age-predicted HRmax. After adjustment, participant intensity selection did not significantly differ by obesity onset when walking or cycling. There were no significant differences in pleasure or perceived exertion by onset, however, perception of exertion was on the high-end of moderate for both the cycle (13.0, 12.5) and treadmill (12.0, 12.1), in JO and AO participants, respectively. Perception of moderate intensity did not differ by obesity onset. Self-selected intensity was at the low end of moderate for walking and cycling.
0 citations (Crossref) [2023-10-31] _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/cob.12492
Keywords: dept.hms; exercise enjoyment; overweight; peer-reviewed; perceived exertion; self-selected intensity; weight loss

Physical Activity, Sports Participation, and Psychosocial Health in Adolescents With Hearing Loss - DeLuca, Zara Waldman; Rupp, Kristie (Journal of Adolescent Health, 2022)
Purpose This study examined the association between hearing status (i.e., adolescents with and without hearing loss) and physical activity and sports participation. Secondarily, we explored the association between physical activity and sports participation and psychosocial outcomes among adolescents with hearing loss. Methods Analyses included 29,034 adolescents (52.1% male, 13.8 ± 2.3 (M ± SD) years) from the combined 2018–2019 National Survey of Children's Health. Adolescents were grouped by hearing status. Adjusted logistic regression models assessed physical activity level (i.e., 0, 1–3, 4–6, and 7 days/week) and sports participation (i.e., participation in sports within the past 12 months) by hearing status. Secondary analyses examined associations between physical activity and sports participation with psychosocial outcomes among adolescents with hearing loss adjusting for relevant confounders. Results Relative to their hearing peers, adolescents with hearing loss (n = 359) were 40% [adjusted odds ratio (AOR), 0.60; 95% confidence interval (CI), 0.44, 0.81], 43% [AOR, 0.57; 95% CI, 0.41, 0.80], and 33% [AOR, 0.67; 95% CI, 0.47, 0.95] less likely to engage in 1–3 days/week of physical activity, 4–6 days/week of physical activity, and meet physical activity guidelines, respectively. Further, adolescents with hearing loss were 31% [AOR, 0.69; 95% CI, 0.55, 0.85] less likely to participate in sports. Sports participation, but not physical activity, was associated with a significant reduction in the likelihood of experiencing adverse psychosocial outcomes among adolescents with hearing loss (p's < .05). Discussion Sports participation, but not physical activity, was associated with attenuated likelihood of experiencing adverse psychosocial outcomes in adolescents with hearing loss, suggesting unique characteristics of sports participation confer protection of psychosocial health. Increasing access to and reducing barriers to engagement in sports should be prioritized to improve psychosocial health in adolescents with hearing loss.
4 citations (Crossref) [2023-10-31]
Keywords: Hearing loss; Physical activity; Psychosocial health; Sports participation; dept.cmd; dept.hms; peer-reviewed

Combining MRI and cognitive evaluation to classify concussion in university athletes - Ly, Monica T.; Scarneo-Miller, Samantha E.; Lepley, Adam S.; Coleman, Kelly; Hirschhorn, Rebecca; Yeargin, Susan; Casa, Douglas J.; Chen, Chi-Ming (Brain Imaging and Behavior, 2022)
Current methods of concussion assessment lack the objectivity and reliability to detect neurological injury. This multi-site study uses combinations of neuroimaging (diffusion tensor imaging and resting state functional MRI) and cognitive measures to train algorithms to detect the presence of concussion in university athletes. Athletes (29 concussed, 48 controls) completed symptom reports, brief cognitive evaluation, and MRI within 72 h of injury. Hierarchical linear regression compared groups on cognitive and neuroimaging measures while controlling for sex and data collection site. Logistic regression and support vector machine models were trained using cognitive and neuroimaging measures and evaluated for overall accuracy, sensitivity, and specificity. Concussed athletes reported greater symptoms than controls (∆R2 = 0.32, p < .001), and performed worse on tests of concentration (∆R2 = 0.07, p < .05) and delayed memory (∆R2 = 0.17, p < .001). Concussed athletes showed lower functional connectivity within the frontoparietal and primary visual networks (p < .05), but did not differ on mean diffusivity and fractional anisotropy. Of the cognitive measures, classifiers trained using delayed memory yielded the best performance with overall accuracy of 71%, though sensitivity was poor at 46%. Of the neuroimaging measures, classifiers trained using mean diffusivity yielded similar accuracy. Combining cognitive measures with mean diffusivity increased overall accuracy to 74% and sensitivity to 64%, comparable to the sensitivity of symptom report. Trained algorithms incorporating both MRI and cognitive performance variables can reliably detect common neurobiological sequelae of acute concussion. The integration of multi-modal data can serve as an objective, reliable tool in the assessment and diagnosis of concussion.
0 citations (Crossref) [2023-10-31]
Keywords: Classification; Concussion; Diffusion tensor imaging (DTI); Mild traumatic brain injury (mTBI); Resting state functional MRI; dept.hms; peer-reviewed

Before-school physical activity program's impact on social and emotional learning - Goh, T.L.; Leong, C.H.; Fede, M.; Ciotto, C. (Journal of School Health, 2022)
BACKGROUND: Despite the positive impact of social and emotional learning (SEL) on the emotional well-being of children, literature on physical activity engagement and SEL among this population has been limited. Therefore, the purpose of this study was to examine whether school students' SEL would improve after participation in a before-school physical activity program. METHODS: A total of 138 fourth and sixth grade students from 1 elementary school and 1 middle school participated in this study. Seventy-five students participated in the before-school physical activity program, while 63 students were in the control group. The physical education teachers implemented the program 3 days per week, for 3 weeks. The participants completed a 10-question adapted Devereux Student Strengths Assessment-Mini before and after the program. Repeated measures ANOVA was run to determine the effects of the program on SEL competence. RESULTS: The fourth and sixth grade students who participated in the program reported a 7 and 10% improvement in pre- versus post-intervention SEL competence, respectively. Students in the control group reported no change in their SEL competence. CONCLUSION: Considering the benefits of a before-school physical activity program on students' SEL, stakeholders should consider including more physical activity programming within school policies. © 2022 American School Health Association.
1 citations (Crossref) [2023-10-31] tex.author_keywords: elementary school; middle school; physical education; social-emotional competence tex.document_type: Article tex.source: Scopus
Keywords: dept.hms; peer-reviewed

Heart rate recovery, central systolic pressure, and augmentation index in young healthy individuals - Latchman, P.L.; Yang, Q.; Kong, L.; Zhang, H.; Sebagisha, J.; De Meersman, R.E. (Vascular Health and Risk Management, 2022)
Purpose: Measuring heart rate recovery (HRR) holds valuable cardiovascular information and requires minimal technical skill and cost. Understanding the associations between HRR and more robust cardiovascular indicators, such as central systolic blood pressure (CSBP), can provide valuable cardiovascular information with less involvement. CSBP is a strong predictor of certain cardiovascular diseases. The study aims to examine the association between measures of HRR and CSBP and the augmentation index (AIx) in a group of young, healthy individuals and based on sex. Participants and Methods: One-hundred and seven participants (men – 55, women – 52) were measured for HRR at one minute (HRR1) and two minutes (HRR2) after maximum oxygen consumption (VO2max) testing, CSBP, and the AIx at a heart rate of 75 beats∙min−1 (AIx@75). Results: The Pearson correlation indicated no association between HRR1, HRR2, and CSBP in men and women combined: r = 0.06, P = 0.53; r = 0.05, P = 0.59, respectively, or based on sex: men = r = 0.01, P = 0.95; r = 0.04, P = 0.79, respectively, and women = r = −0.05, P = 0.75; r = −0.09, P = 0.52, respectively. However, there were associations between HRR1 and AIx@75 in men and women combined: r = −0.37, P < 0.001, and based on sex: men = r = −0.31, P = 0.02, and women = r = −0.38, P < 0.01. Conclusion: Measures of HRR were not associated with CSBP in a combined group of young men and women or based on sex. Most measures of HRR, especially those established by parasympathetic nervous activity, were associated with lower AIx@75. Though measures of HRR might be good indicators of cardiovascular disease, they might not be good indicators of CSBP in young, healthy individuals. © 2022 Latchman et al.
3 citations (Crossref) [2023-10-31] tex.author_keywords: Augmentation index; Central blood pressure; Central systolic blood pressure; Heart rate recovery; Sex tex.document_type: Article tex.pubmed_id: 35173435 tex.source: Scopus
Keywords: Article; Blood Pressure; Cardiovascular Diseases; Cardiovascular System; Female; Heart Rate; Humans; Male; adult; augmentation index; blood pressure; cardiovascular disease; cardiovascular parameters; cardiovascular system; central systolic pressure; cholinergic system; controlled study; dept.hms; diastolic blood pressure; female; heart rate; heart rate recovery; heart rate variability; human; human experiment; male; maximal oxygen uptake; normal human; peer-reviewed; predictive value; sex difference; systolic blood pressure; young adult